Pengaruh Physical Evidence Terhadap Keputusan Pembelian Konsumen Pada Warkop Sri Pandita - Ashari, Aprilia Suci; Jamiat, Nuslih (eProceedings of Management, 2024)
This study aims to determine how the influence of Physical Evidence on consumer purchasing decisions at WarkopSri Pandita. This research uses quantitative research with descriptive research type and sampling using NonProbability Sampling technique using Purposive Sampling method with a total of 100 respondents of Warkop SriPandita consumers. With simple linear regression data analysis techniques using IBM SPSS Statistics 25 software.The results of partial testing (t test) the Physical Evidence variable has a significant effect with a Thitung of 8.024>Ttable 1988 and a significance level of 0.000 <0.05. Based on the coefficient of determination that Physical Evidencehas an influence on purchasing decisions by 39.6%, while the remaining 60.4% is influenced by other variables notexamined.Keywords-physical evidence, purchase decision, consumer